The impact of the oil price on mineable and non-mineable cryptocurrencies - Unal, Emre; Kose, Nezir (Taylor & Francis Inc, 2023)
The digital world has become an inevitable part of daily life. With cryptocurrencies, a new investment opportunity has emerged around the globe. Extending digital life increases the energy demand. These new assets consume a considerable amount of energy resources. The mining process in particular can be significantly affected by energy prices. The purpose of this work is to reveal the impact of the oil price on mineable and non-mineable cryptocurrencies which would provide insight for policymakers, investors, miners, and portfolio managers. This research utilized a panel cointegration model and panel Granger causality tests to the daily data collected between May 11, 2021 and June 23, 2022. 15 mineable and 19 non-mineable cryptocurrencies were selected for the study. Other variables include the oil price, the VIX, and the gold price. The research indicated that there is a negative correlation between the oil price and cryptocurrencies. The VIX had a negative effect in the short term, whereas the gold price had a positive and significant correlation in the long term. The impact of the oil price on mineable cryptocurrencies was larger than that on non-mineable cryptocurrencies. This means that alternative energy resources are essential to reduce the dependency of cryptocurrencies on this type of fossil fuel.
Keywords: Cryptocurrency; mineable and non-mineable; panel granger causality test; oil price; VIX